Performance of Post-Fire Composite Prestressed Concrete Beam Topped with Reinforced Concrete Flange - Nibras Abbas Harbi; Amer F. Izzet (Salehan Institute of Higher Education, 2018)
The performance of composite prestressed concrete beam topped with reinforced concrete flange structures in fire depends upon several factors, including the change in properties of the two different materials due to fire exposure and temperature distribution within the composition of the composite members of the structure. The present experimental work included casting of 12 identical simply supported prestressed concrete beams grouped into 3 categories, depending on the strength of the top reinforced concrete deck slab (20, 30, and 40 MPa). They were connected together by using shear connector reinforcements. To simulate the real practical fire disasters, 3 composite prestressed concrete beams from each group were exposed to high temperature flame of 300, 500, and 700°C, and the remaining beams were left without burning as reference specimens. Then, the burned beams were cooled gradually by leaving them at an ambient lab condition, after which the specimens were loaded until failure to study the effect of temperature on the residual beams serviceability, to determine the ultimate load-carrying capacity of each specimen in comparison with unburned reference beam, and to find the limit of the temperature for a full composite section to remain composite. It was found that the exposure to fire temperature increased the camber of composite beam at all periods of the burning and cooling cycle as well as the residual camber, along with reduction in beam stiffness and the modulus of elasticity of concrete in addition to decrease in the load-carrying capacity.